Adaptation and cross-cultural validationof the United States Primary Care Assessment Tool (expanded version) for use in South Africa - Graham Bresick; Abdul-Rauf Sayed; Cynthia le Grange; Susheela Bhagwan; Nayna Manga (AOSIS, 2015)
Background: Measuring primary care is important for health sector reform. The Primary Care Assessment Tool (PCAT) measures performance of elements essential for cost-effective care. Following minor adaptations prior to use in Cape Town in 2011, a few findings indicated a need to improve the contentand cross-cultural validity for wider use in South Africa (SA). Aim: This study aimed to validate the United States of America-developed PCAT before being used in a baseline measure of primary care performance prior to major reform. Setting: Public sector primary care clinics, users, practitioners and managers in urban and rural districtsin the Western Cape Province. Methods: Face value evaluation of item phrasing and a combination of Delphi and Nominal Group Technique (NGT) methods with an expert panel and user focus group were used to obtain consensus on content relevant to SA. Original and new domains and items with > = 70% agreement were included in the South African version - ZA PCAT. Results: All original PCAT domains achieved consensus on inclusion. One new domain, the primary healthcare (PHC) team, was added. Three of 95 original items achieved < 70% agreement, that is consensus to exclude as not relevant to SA; 19 new items were added. A few items needed minor rephrasing with local healthcare jargon. The demographic section was adapted to local socio-economic conditions. The adult PCAT was translated into isiXhosa and Afrikaans. Conclusion: The PCAT is a valid measure of primary care performance in SA. The PHC team domainis an important addition, given its emphasis in PHC re-engineering. A combination of Delphi and NGT methods succeeded in obtaining consensus on a multi-domain, multi-item instrument in a resource-constrained environment.